Analisis Faktor Kriminogen dalam Kasus Pembunuhan Berencana terhadap Pasangan : Studi Kasus Pembunuhan Berencana di Kelurahan Mata Air, Kecamatan Reok, Kabupaten Manggarai - Jihan Fahira; Orpa Ganefo Manuain; Sigit Prabowo Sonbait (AKADEMIK: Jurnal Mahasiswa Humanis, 2026)
Premeditated murder within intimate relationships reflects complex criminogenic conditions that are often rooted in personal and social dynamics. This study aims to identify the factors influencing perpetrators in committing premeditated murder against their partners and to examine efforts to prevent and control such crimes. The research employs an empirical legal method with a sociological approach, conducted in Manggarai Regency. Primary data were obtained through interviews with eight respondents, including the perpetrator, investigators, witnesses, correctional officers, and a legal expert, and supported by secondary data from relevant literature and legal documents. The findings indicate that premeditated murder is influenced by the interaction of personal and situational factors. Personal factors include psychological pressure, emotional instability, jealousy, and dissatisfaction in marital relationships. Meanwhile, situational factors involve persistent domestic conflict, economic hardship, and an unsupportive family environment. Crime prevention efforts are implemented through both penal and non-penal approaches. Penal measures focus on law enforcement processes to ensure legal certainty and deterrence, while non-penal measures emphasize preventive actions such as legal awareness, counseling, and conflict mediation. An integrated approach combining these strategies is essential for effective and sustainable crime prevention.